Evaluasi Kinerja Instalasi Rehabilitasi Medik Berbasis Balanced Scorecard di Rumah Sakit Umum Indonesia - Jotlely, Herly; Herwawan, Joan Herly; Nindatu, Maria; Tasijawa, Fandro Armando (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Medical rehabilitation services are one of the key pillars of the healthcare system, particularly in supporting patient recovery and preventing long-term disability. However, this unit often receives insufficient attention in hospital performance evaluations. This study aims to assess the performance of the Medical Rehabilitation Unit at RSUD Dr. M. Haulussy using the Balanced Scorecard (BSC) approach, which comprises four perspectives: learning and growth, internal business processes, customers, and finances. A quantitative research design was employed using questionnaire instruments and descriptive analysis involving 50 employee respondents and 100 patients. The findings show that, within the learning and growth perspective, there is a commitment to human resource development through training, although access to such opportunities remains uneven. The internal business process perspective highlights weaknesses in service innovation, adequacy of facilities, and continuity of patient care. From the customer perspective, the unit demonstrates a broad market share and a strong growth rate of new patients; however, patient retention and satisfaction levels remain moderate. In the financial perspective, the unit’s contribution to overall hospital revenue is still low (16%), despite clear potential for developing new services. Overall, the BSC evaluation indicates that the Medical Rehabilitation Unit is performing at a moderately good level but requires improvements in facilities, service innovation, staff engagement, and financial strategies to enhance service quality and strengthen its contribution to the hospital.